2003
DOI: 10.1055/s-2003-37192
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitric Oxide in the Mechanism of Preclamping and Remote Ischemic Preconditioning of Adipocutaneous Flaps in a Rat Model

Abstract: The purpose of this study was to determine whether nitric oxide (NO) plays a role in the mechanism of acute ischemic preconditioning (IP). Fifty-eight male Wistar rats were divided into seven experimental groups. An extended epigastric flap was raised in one of the control groups (C, n = 8), and a 3-hr flap ischemia was induced. Another group served as a non-ischemic control (CO, n = 8). The animals of group S (n = 9) received 500 nmol/kg of Spermine/Nitric Oxide Complex (Sper/NO) intravenously 30 min prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Nitric oxide has an important role in delayed remote cardioprotection 22 and in the early protection of adipocutaneous flaps with limb RIPC 11 . The role of nitric oxide in early remote cardioprotection is controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitric oxide has an important role in delayed remote cardioprotection 22 and in the early protection of adipocutaneous flaps with limb RIPC 11 . The role of nitric oxide in early remote cardioprotection is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…RIPC of the limb in humans 8 and animals 9 reduces IRI to the heart, lungs and other organs 10 . A putative role for nitric oxide has been suggested 11 . The present study investigated the possible effect of RIPC of the hind limb in reducing the adverse effects of warm liver IRI, and the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Eight studies have demonstrated the beneficial effect of skeletal preconditioning on adipocutaneous, muscle, and cremasteric muscle flaps as well as remote skeletal tissue [47][48][49][50][51][52][53][54]. Moses et al [47] demonstrated reduced LD muscle flap infarct size in a pig model following RIPC (3 ϫ 10 min).…”
Section: Role Of Mesenteric Ipc (Table 4)mentioning
confidence: 99%
“…The role of NO in IPC has been proposed in several studies, although the exact mechanism is unknown [23,[40][41][42][43]. On the other hand, in R-IPC the role of NO is more debatable; although it has been proposed as the mechanism for R-IPC in the heart and adipo-cutaneous flaps, others have rejected this [44][45][46]. In the settings of liver IRI, only one study has found evidence for the role of NO in the protective effect of R-IPC [15].…”
Section: Discussionmentioning
confidence: 99%